Acquiring E-Books for academic libraries - Woodward, Hazel (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
This paper outlines the recent work of the UK’s Joint Information Systems Committee ( JISC) in the area of e-books. The JISC Collections Team is responsible for negotiating deals with publishers and aggregators of e-content for all UK higher education libraries - some 180 in total. In other words it acts as a national consortium for the UK academic community, although it should be noted that all deals are negotiated on an ‘opt-in’ basis. The JISC Collections Team is advised by a series of format-based working groups - comprising senior academic librarians and library practitioners - including the E-Books Working Group, the Journals Working Group and the Moving Images Working Group. Recently the working groups have formulated vision statements to help inform both their own activities and the education community as a whole. The vision for e-books in UK education is as follows: “The UK education community will have access to quality e-book content that is of high relevance to teaching, learning and research across the broadest range of subject areas. Flexible business and licensing models will support a diversity of needs, allowing users to do what they want when they want and how they want for education purposes. All e-books will be easily discoverable and consistent standards will allow all content to be fully integrated into library, learning and research environments.”